Environmental friendly Takakura home method composter for food waste reduction - Hashim, Nor Haslina; Abdul Talib, Muhammad Ammar; Tuan Ismail, Tuan Noor Hasanah; Abdullah, Nor Maizzaty (Penerbit UTHM, 2020)
The disposal of waste at landfill site is to minimize environmental impact and the main purpose of it is using sanitary method as the last implementation for disposal [1], in general that is the place for pile up garbage, rubbish or trash with proper design. There also have other disposal place for Malaysia occupant that called dump site which is the dump site is illegal place for disposal of waste but often exist at abandon area. During the 20th century, there were significant technological developments in composting. The earliest composting systems did not employ mechanization, but rather relied on hand labor. Records of the very earliest composting systems are mostly anecdotal, but historical composting systems have been reported in contemporary literature. One example is the composting system built in 1787 at his Mount Vernon, Va., estate by George Washington, the first president of the United States..